Predicting vibration characteristics of a bolted pipe assembly with complex boundary and interface constraints via the frequency based substructuring method - Sudin, Mohamad Affendi; Mohd Kahar, Muhammad Syafiq Aiman; Kyprianou, Andreas; Wan Iskandar Mirza, Wan Imaan Izhan; Yunus, Mohd Azmi; Febrina, Rina; Mutra, Rajasekhara Reddy; Abdul Rani, Muhamad Norhisham (UiTM Press, 2025)
Accurately coupling Finite Element Frequency Response Functions (FE-FRFs) with Experimental Modal Analysis Frequency Response Functions (EMA-FRFs) reduces analytical modelling complexity and improves the accuracy of vibration characteristic predictions for complex structures. However, coupling these two different resources remains a major challenge due to complex boundary constraints and bolted joints, which are common in aerospace, automotive, and civil engineering applications. To address these challenges, this study proposes a methodology that integrates the Finite Element Method (FEM), Experimental Modal Analysis (EMA), and Frequency-Based Substructuring (FBS) for accurate and systematic coupling of FE and EMA FRFs. The methodology is demonstrated using a Bolted Flanged Pipe Assembly (BFPA), consisting of a Flanged Elbow Pipe (FEP) and a Flanged Pipe (FP) as a case study. The FE model of the FP substructure is carefully constructed to include coupling interfaces, and its FRFs are computed under free-free boundary constraints. Meanwhile, the FRFs of the FEP substructure, which is extremely difficult to model analytically, are measured using EMA under fixed-free boundary constraints. To achieve accurate coupling, formulations based on the FBS method are developed to integrate FRFs from these two different sources, enabling the prediction of the coupled FRF of the BFPA. Furthermore, EMA is performed on the BFPA to measure its FRFs, which serve as a benchmark. The reliability of the proposed methodology is evaluated by the EMA benchmark. The results confirm that the methodology effectively and accurately represents the measured FRF. Its potential applications include accelerated product development, enhanced performance, and improved safety, benefiting industries that rely on precise structural modelling.